Ecology of Mabuya agilis (Raddi) (Lacertilia, Scincidae) at the restinga of Grumari, Rio de Janeiro, southeastern Brazil - Vrcibradic,Davor (2002)
Some aspects of the ecology of the skink Mabuya agilis (Raddi, 1823) at the restinga habitat of Grumari, in Rio de Janeiro, Brazil are studied. Most of the lizards were first sighted on the ground, though a few were using perches (mainly cacti) up to 30 cm high. Mean body temperature in activity was 33.1 ± 2.4ºC and was significantly correlated to air temperature. There was sexual dimorphism in size (snout-vent length - SVL), with females growing larger than males. Frequency of broken tails was high overall (83%) and did not differ between sexes. Females and males are sexually mature at 49 mm and 47 mm SVL, respectively. Brood size averaged 3.2 ± 1.0 (range 1-5) and was positively and significantly related to female SVL (r = 0.65, p = 0.001). Relative clutch mass (RCM) of seven gravid females averaged 0.250 ± 0.042, being relatively low compared to those of other congeners. The diet of M. agilis was composed basically of arthropods, with relatively large and soft-bodied arthropods such as spiders, caterpillars and homopterans being the most important prey. The results of our work confirm and expand the knowledge of ecological tendencies previously observed for M. agilis in other areas.